Foundations of BizTalk Server 2006 - Woolston, Daniel (Apress, 2012)
Ihave always been a fan of complexity. Some people fear and avoid it, but for some strange reason, I thrive on it. I’m a huge fan of puzzle games and typically have a Rubik’s Cube well within reach to satiate my need for concentrated problem-solving. It’s a strange obsession that many of you, my brothers and sisters in technology, share. We excel at coding and application integration because we feed on the detailed process by which we deliver our products. Many of the things that we accomplish may seem impossible at first, but numerous hours (and gallons of caffeine) later, we roll out a product or plan that we’re proud to put our name on. And we do that because we love complexity. I was drawn to BizTalk Server because I had heard many developers and architects say that the product was difficult to learn and had a deep level of intricacy. Few people were interested in learning the product, so I felt as if the gauntlet had been thrown. I told myself, “This truly is a product worth learning, if it’s as hard as they say.” Years later, I’ve found that it is, indeed, an excellent application deserving of obsession. I have also discovered that as you peel back the layers of BizTalk Server, it becomes a very intuitive product to use. This book will help you to do just that. We’ll investigate BizTalk Server in manageable chunks, so that you’re able to decipher and understand each of the individual puzzle pieces (or components) that, together, form the BizTalk Server 2006 product.